Unravelling mechanisms for the formation of amorphous bands in B6O under nonhydrostatic pressure. (1st March 2022) - Han, Yunxia; Gu, Chao; Chen, Jian; Zhou, Xuefeng; Ma, Dejiang; Cheng, Hu; Zhao, Yusheng; He, Duanwei; Wang, Shanmin
Abstract: Boron suboxide (B6 O) with superhardness holds great promise for a wide range of practical applications, but suffers from a low fracture toughness due to the formation of unusual nanoscale amorphous bands. Understanding of the underlying deformation mechanisms in this material, however, has been hindered limited experimental evidences. Here we report the discovery of new mechanisms for the formation of amorphous bands in B6 O under nonhydrostatic pressure, based on in-situ high-pressure optical absorption measurements and analysis of postmortem samples. We find that the bandgap of B6 O is sensitive to plastic deformation, offering an effective approach for exploring deformation behaviors of this material. Two new amorphous bands are identified along two distinct crystallographic planes of ( 1 1 ¯ 0 4 ¯ ) and ( 4 3 ¯ 1 ¯ 8 ¯ ) associated with unbonded O-O pairs. Our findings establish a methodology for in-situ probe of plastic deformation in brittle materials, and demonstrate how their properties can be altered by plastic deformations under nonhydrostatic pressures. Graphical abstract: Image, graphical abstract